Mengurai Nilai-Nilai Moderasi Beragama Dalam Tafsir Al-Azhar (Analisis Hermeneutik Hans Georg-Gadamer) - Sihombing, Muhammad Ebin Rajab; Sihombing, Amrina; Mastika Rambe (Pusat Kajian Moderasi Beragama dan Ideologi Pancasila UIN Sulthan Thaha Saifuddin Jambi, 2023)
Indonesia as a multi-religious country has encountered extraordinary challenges, both external and internal, in its journey to religious communities. An important aspect of this research is exploring the value of religious moderation in the interpretation of al-Azhar and analyzing it using Hans-Georg Gadamer's hermeneutical approach. This research focuses on studying moderation verses using qualitative methods such as literature review. This research found that the value of religious moderation contained in al-Azhar's interpretation is balance between worldly life and the afterlife, being in the middle of worship and being wise with local culture. Merging the horizons between Buya Hamka and the text, a concept of religious moderation that is balanced in the vertical and horizontal realms is born so that the value of religious moderation can be used as a basis for thinking, behavior and evaluation material.